Exploring Sentinel-1 backscatter time series over the Atacama Desert (Chile) for seasonal dynamics of surface soil moisture - Ullmann, Tobias; Jagdhuber, Thomas; Hoffmeister, Dirk; May, Simon Matthias; Baumhauer, Roland; Bubenzer, Olaf (Remote sensing of environment, 2022)
Recent research indicates an inverse relation between Synthetic Aperture Radar (SAR) signal and near-surface soil moisture (SM) over very dry sediments, arid to hyper-arid soils resp., caused by subsurface scattering effects. This phenomenon can lead to large errors when it comes to modelling and remote sensing-based estimation of SM. While the effect of subsurface scattering and its influence on SM estimates is well described and modelled in literature, its actual presence in recorded SAR data is largely unknown. Here we investigate the relation between C-Band SAR backscatter and SM in the hyper-arid environment of the Atacama Desert (Chile). Time series (2018-2020) of Sentinel-1 VV/VH intensities are compared to in situ SM, measured at 17 stations located across the Atacama Desert. Linear and non-linear regression modelling is applied to uncover the relationship between the SAR intensities and in situ SM, while, in addition, SM variations triggered by seasonal varying humidity (i.e., not by precipitation) are investigated. Results indicate (i) a very weak linear relationship between SM variations and SAR intensities (VV/VH) for most meteorological stations in the Atacama (R2 < 0.5). In particular, noticeable and significant exceptions are found for stations located in the northern uplands of the Coastal Cordillera and on sediments, which are characterized by thick atmospheric dust deposits on top of subsurface cemented crusts; (ii) over these sites a strong inverse linear relationship is present (R2 up to 0.84) and the observable seasonal variations in SAR intensity are linked to the seasonal variations in SM; (iii) remarkably low changes in SM (ranging from approx. 1 to 3%) lead to comparable high changes in SAR intensity (up to 5.5 dB in VH and up to 4.0 dB in VV); (iv) employing a non-linear regression modelling to the SAR time series allowed identifying the occurrence and the strength of seasonal variations over the central desert. This study contributes to a better understanding of SAR scattering over arid to hyper-arid soils, indicates a moisture-regulated complex interplay of surface and subsurface scattering, and proves the presence of subsurface scattering effects in Sentinel-1C-Band data to occur over large parts of the Atacama Desert.
Gesehen am 31.03.2023